Optimizing aircraft departure and arrival sequencing using genetic algorithms - Ng, Timothy Jefferson Wei Han (2014)
With a major increase in air transport projected over the next few decades, there is an increasing need for airports to fully utilize their throughput by minimizing the time required for a given set of aircraft to land on a runway.